Body Size Is Positively Correlated With Conspicuous Coloration in Ambystoma Salamanders, but Negatively Correlated With Conspicuous Coloration in Plethodon Salamanders - Winebarger, Monica M.; Pugh, M. Worth; Gangloff, Michael M.; Osbourn, Michael S.; Siefferman, Lynn (Frontiers in Ecology and Evolution, 2018)
Conspicuous coloration coupled with secondary defensive mechanisms is known as aposematic coloration and is used in predator avoidance and defense. Classic theory argues that aposematic signals tend to be more effective in larger organisms as they are intrinsically more easily detected by predators and are also more profitable prey items. Thus, it has been hypothesized that conspicuous coloration evolves in tandem with increased body size in aposematic prey because this likely increases the visibility and efficacy of the signal. To test this hypothesis, we used a comparative phylogenetic approach to investigate associations between body size and conspicuous coloration in two North American salamander genera: Ambystoma and Plethodon, both of which secrete noxious compounds to deter predators. Our analyses showed that increased conspicuous coloration co-evolved with increased body size in Ambystoma, yet we found the opposite relationship in the Plethodon clade. We speculate this is likely because Ambystoma are generally larger than Plethodon and exhibit gregarious mating behavior. Future studies should explore the toxicity of slimy skin secretions and how this may contribute to aposematic signaling in salamanders.